Gambaran Pengetahuan dan Minat Donor Darah Mahasiswa Fakultas Kesehatan Universitas Jenderal Achmad Yani Yogyakarta - Nurinayah Nurinayah; Nur’Aini Purnamaningsih; Ratna Prahesti (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT Blood donation is the process of taking blood from someone voluntarily for transfusion to someone in need. Students studying in the field of health science have a role to serve the community, one of which is through voluntary blood donation activities and taking steps to raise awareness regarding blood donations among other student communities so that recruitment efforts will be more effective. Currently, Jenderal Achmad Yani University does not have a record of routine blood donors. This study aims to describe the knowledge and interest of blood donors from health faculty student at the Jenderal Achmad Yani University, Yogyakarta. This research is a quantitative study with a cross sectional approach. The sample was 94 people and the sample was taken using simple random sampling. Data collection tools and methods used a questionnaire of knowledge and interest in blood donors. Univariate data analysis techniques. The results showed that the percentage of students with good knowledge was 45 people (47,9%), student with sufficient knowledge was 46 people (48,9%), and student with poor knowledge were 3 people (3,2%). For the results, the percentage of students with high interest is 76 people (80,9%, 15 students with moderate interest (16,0%) and 3 students with low interest (3,2%). Students of the Faculty of Health, Universitas Jenderal Acmad Yani Yogyakarta who have good knowledge are 45 people (47.9%), students with sufficient knowledge are 46 people (48.9%), and students with less knowledge are 3 (3.2%). High interested students are 76 people (80.9%), students with moderate interest are 15 (16.0%), and students with low interest are 3 people (3.2%).          Keywords: Knowledge; interest; blood donation; students  ABSTRAK Donor darah adalah proses pengambilan darah dari seseorang secara sukarela untuk ditransfusikan kepada seseorang yang membutuhkan. Mahasiswa yang belajar dalam bidang ilmu kesehatan memiliki peran untuk mengabdi kepada masyarakat salah satunya dengan kegiatan donor darah sukarela dan mengambil langkah untuk meningkatkan kesadaran terkait donor darah di antara komunitas mahasiswa lainnya sehingga upaya rekrutmen akan lebih efektif. Saat ini Universitas Jenderal Achmad Yani belum memiliki catatan pendonor darah rutin. Penelitian ini bertujuan untuk mengetahui gambaran pengetahuan dan minat donor darah mahasiswa Fakultas Kesehatan Universitas Jenderal Achmad Yani Yogyakarta. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross-sectional. Sampel berjumlah 94 orang dan sampel diambil dengan menggunakan simple random sampling. Alat dan metode pengambilan data dengan menggunakan kuesioner pengetahuan dan minat donor darah. Teknis analisis data  secara univariat. Tingkat pengetahuan mahasiswa yang berpengetahuan baik 45 orang (47,9%), mahasiswa berpengetahuan cukup 46 orang (48,9%), dan mahasiswa berpengetahuan kurang 3 orang (3,2%). Untuk hasil persentase mahasiswa yang berminat tinggi 76 orang (80,9%), mahasiswa yang berminat sedang 15 orang (16,0%), dan mahasiswa yang berminat rendah 3 orang (3,2%). Mahasiswa Fakultas Kesehatan Universitas Jenderal Achmad Yani Yogyakarta yang berpengetahuan baik adalah 45 orang  (47,9%), mahasiswa berpengetahuan cukup 46 orang (48,9%), dan mahasiswa berpengetahuan kurang 3 orang (3,2%). Mahasiswa yang berminat Tinggi adalah tinggi 76 orang (80,9%), mahasiswa yang berminat sedang 15 orang (16,0%), dan mahasiswa yang berminat rendah 3 orang (3,2%). Kata kunci: Pengetahuan; minat; donor darah; mahasiswa